Pemenuhan Asas Keadilan Dalam Penerapan Parliamentary Threshold Pada Pemilihan Umum Legislatif di Indonesia - Salim, Patrick Winson; Sitabuana, Tundjung Herning (JURNAL USM LAW REVIEW, 2024)
The purpose of this study is to analyze and find out the application of the parliamentary threshold in Law No. 7 of 2017 and Constitutional Court Decision Number 116/PUU-XIX/2023 and evaluate whether its application meets the principles of justice. This is motivated by the application of the parliamentary threshold regulated in Law No. 7 of 2027 on General Elections and reaffirmed through Constitutional Court Decision Number 116/PUU-XIX/2023 which is considered not fulfilling the principle of justice and violating the 1945 Constitution. The urgency of this research is to provide legal clarity regarding the parliamentary threshold, which is intended to maintain the quality of representation in parliament, but in practice creates problems of injustice for parties that are unable to meet the threshold. The novelty in this author's research is to show that the application of the parliamentary threshold can reduce the diversity of political choices and affect the fairness of representation. The research method used in this study is the normative method. The results show that the application of the parliamentary threshold in Law No. 7/2017 and Constitutional Court Decision Number 116/PUU-XIX/2023 reflects the Court's efforts to consider the principle of justice. Stating that the threshold is still needed, but it must be reviewed to ensure more proportional and democratic representation. This is in line with the concept of justice according to philosophers who view that the review of the threshold also aims to provide opportunities for underrepresented parties, support the principle of justice as fairness, and achieve justice that allows future parliamentary thresholds to be determined based on popular sovereignty. Tujuan pada penelitian ini adalah untuk menganalisis dan mengetahui penerapan parliamentary threshold dalam UU No. 7 Tahun 2017 dan Putusan MK Nomor 116/PUU-XIX/2023 serta mengevaluasi apakah penerapannya memenuhi asas keadilan. Hal ini dilatarbelakangi oleh penerapan ambang batas parlemen yang diatur dalam UU No. 7 Tahun 2027 tentang Pemilihan Umum dan ditegaskan kembali melalui Putusan MK Nomor 116/PUU-XIX/2023 yang dianggap tidak memenuhi asas keadilan dan melanggar Undang-Undang Dasar Tahun 1945. Urgensi penelitian ini ialah memberikan kejelasan secara hukum mengenai parliamentary threshold yang dimaksudkan untuk menjaga kualitas representasi di parlemen dalam praktiknya justru menciptakan permasalahan ketidakadilan bagi partai-partai yang tidak mampu memenuhi ambang batas tersebut. Kebaruan dalam penelitian penulis ini adalah menunjukkan bahwa penerapan parliamentary threshold dapat mereduksi keberagaman pilihan politik dan memengaruhi keadilan representasi. Metode penelitian yang digunakan dalam penelitian ini adalah metode normatif. Hasil penelitian menunjukkan bahwa penerapan parliamentary threshold dalam UU No. 7 Tahun 2017 dan Putusan MK Nomor 116/PUU-XIX/2023 mencerminkan upaya MK mempertimbangkan asas keadilan. Menyatakan ambang batas tetap diperlukan, tetapi harus ditinjau untuk memastikan representasi yang lebih proporsional dan demokratis. Hal tersebut sejalan dengan konsep keadilan menurut filsuf-filsuf yang memandang peninjauan ambang batas juga bertujuan memberi kesempatan bagi pihak yang kurang terwakili, mendukung prinsip justice as fairness serta mencapai keadilan yang memungkinkan parliamentary threshold masa depan ditetapkan berdasarkan kedaulatan rakyat.